Fractional-Calculus-Based FDTD Algorithm for Ultrawideband Electromagnetic Characterization of Arbitrary Dispersive Dielectric Materials - Karatelli (Caratelli) D. Diego; Mescia L. Luciano; Bia P. Pietro; Stukach O. V. Oleg Vladimirovich (2016, 2016)
Title screen